Taking 5G RAN Analytics and Control to a New Level - Foukas, Xenofon; Radunovic, Bozidar; Balkwill, Matthew; Lai, Zhihua (ACM MobiCom 2023, 2023)
Open RAN, a modular and disaggregated design paradigm for 5G radio access networks (RAN), promises programmability through the RAN Intelligent Controller (RIC). However, due to latency and safety challenges, the telemetry and control provided by the RIC is mainly limited to higher layers and higher time scales (>10ms), while also relying on predefined service models which are hard to change. We address these issues by proposing Janus, a fully programmable monitoring and control system, specifically designed with the RAN idiosyncrasies in mind, focused on flexibility, efficiency and safety. Janus builds on eBPF to allow third-parties to load arbitrary codelets inline in the RAN functions in a provably safe manner. We extend eBPF with a novel bytecode patching algorithm that enforces codelet runtime thresholds, and a safe way to collect user-defined telemetry. We demonstrate Janus' flexibility and efficiency by building 3 different classes of applications (18 applications in total) and deploying them on a 100MHz 4x4 MIMO 5G cell without affecting the RAN performance.